Real-time monitoring of electrochemically induced calcium carbonate depositions: Kinetics and mechanisms. (20th February 2021) - Liu, Zilong; Onay, Hayati; Guo, Fengzhi; Lv, Qichao; Sudhölter, Ernst J.R.
Abstract: Calcium carbonate (CaCO3 ) deposition plays a significant role in processes such as scale formation in power plants and in oil or gas production wells. The development of appropriate methods based on well suitable in situ sensors is important to evaluate and predict the deposition process. In this study, a combination of electrochemical techniques and quartz crystal microbalance with dissipation monitoring (QCM-D) in one analysis setup (EQCM-D) was used for the first time to monitor the CaCO3 deposition in real time and provide kinetic details of the CaCO3 deposition process. Through recording the frequency change of quartz crystal sensors, it allows us to perform a quantitative analysis of the morphology, coverage, deposition rate, and mass changes with nanogram sensitivity. By varying the applied voltage, it was found that a lower applied voltage resulted in more deposition of CaCO3 mass and increase of the thickness of the deposited layer. Under the absence of flow, the CaCO3 growth rate switched from accelerating to decelerating and this point is characterized by an inflection point (IP). A lower applied voltage resulted in a lower IP. Increasing Ca 2+ and HCO3 − concentrations, both the deposited amount of CaCO3 mass and coating thickness increased correspondingly. With the addition of 50 mM Mg 2+, a reduction in the deposition rate of CaCO3 as high as 73% was achieved. The higher the Mg 2+ concentration, the larger the deposition rate reduction, which was attributed to the incorporation of Mg 2+ into the growing CaCO3 mineral, resulting in the reduction of growth sites (inhibiting effect). The obtained results contribute to a better understanding of electrochemically induced CaCO3 deposition and provide valuable insights into the determination of optimal precipitation parameters, with the aim to optimize industry scaling and anti-scaling processes.